HUBUNGAN ANTARA PERILAKU BULLYING DENGAN KEPERCAYAAN DIRI SISWA KELAS VII DAN VIII SMP NEGERI 4 SOMAMBAWA - Fatoroli Ndruru (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
This research was motivated by bullying behavior and low self-confidence of students at SMP Negeri 4 Somambawa. The aim of the research is to determine the relationship between bullying behavior and students' self-confidence at SMP Negeri 4 Somambawa academic year. The type of research used is quantitative research with an associative type. Research results: there is a relationship between bullying behavior and students' self-confidence at SMP Negeri 4 Somambawa academic year, meaning that the impact of bullying behavior can reduce students' levels of self-confidence, and is proven by the results of the hypothesis calculation tcount= 7.751 >ttable= 2.064 which means Ha accepted and H0 rejected. Suggestions: 1) For victims of bullying, if they experience bullying behavior, they should be brave enough to report it to the school, such as the homeroom teacher or guidance counselor, so that the perpetrator gets a deterrent effect and does not repeat the behavior. 2) For perpetrators of bullying, they should no longer carry out bullying behavior because it can harm themselves and others. 3) It is hoped that guidance and counseling teachers can improve counseling services to prevent bullying behavior and increase self-confidence. 4) For schools, guidance and counseling teachers should schedule at least one meeting with 2 lesson hours (JP) every week in each class, so that bullying behavior can be reduced.